Integrating Evidence of the Traditional Chinese Medicine Collateral Disease Theory in Prevention and Treatment of Cardiovascular Continuum - Cheang, Iokfai; Liao, Shengen; Zhu, Qingqing; Ni, Gehui; Wei, Cong; Jia, Zhenhua; Wu, Yiling; Li, Xinli (Frontiers in Pharmacology, 2022)
Cardiovascular disease has become a major public health problem. The concept of "cardiovascular continuum" points out the process from high-risk factors that lead to arteriosclerosis, vulnerable plaque rupture, myocardial infarction, arrhythmia, heart failure, and death. These characteristics of etiology and progressive development coincide with the idea of "preventing disease" in traditional Chinese medicine, which runs through the process of systemic intervention. With the update of the understanding via translational medicine, this article reviews the current evidence of the collateral disease theory set prescriptions in mechanism and clinical application, which is expected to lead to the development of new therapeutic strategies for prevention and treatment.